Analysis of experience in employing the networked teaching/learning method in the applied mathematics - Kastickaitė, Joana; Krylovas, Aleksandras; Norvaišas, Saulius; Laukevičius, Tadas (Lietuvos matematikos rinkinys, 2012)
This article describes the first experience with networked teaching/learning method Applied Mathematics course in teaching. Of networked teaching/learning method provides an active students and teacher use of online technologies and special software. The method of mathematics courses is not a trivial matter and requires a search for new didactic solutions.